Generating Novelty Through Interdependent Routines: A Process Model of Routine Work - Deken, Fleur; Carlile, Paul R.; Berends, Hans; Lauche, Kristina (Organization Science, 2016)
We investigate how multiple actors accomplish interdependent routine performances directed at novel intended outcomes and how this affects routine dynamics over time. We report findings from a longitudinal ethnographic study in an automotive company where actors developed a new business model around information-based services. By analyzing episodes involving interdependent routines, we develop a process model of routine work and dynamics across routines. We identify three types of routine work (flexing, stretching, and inventing) that generate increasingly novel actions and outcomes. Flexed, stretched, and invented performances create emerging consequences for further actions across routines and surface differences between actors that could lead to breakdowns of routine work. Actors respond to such consequences through iterative and cascading episodes of routine work. We discuss how our findings provide new insights in efforts to create variable routine performances and the consequences of interdependence for routine dynamics.